2018
DOI: 10.1016/j.jshs.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in lifelong trained male football players compared with young and elderly untrained men

Abstract: PurposeThe purpose of the present controlled cross-sectional study was to investigate proximal femur and whole-body bone mineral density (BMD), as well as bone turnover profile, in lifelong trained elderly male football players and young elite football players compared with untrained age-matched men.MethodsOne hundred and forty healthy, non-smoking men participated in the study, including lifelong trained football players (FTE, n = 35) aged 65–80 years, elite football players (FTY, n = 35) aged 18–30 years, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…The results from the reviewed studies showed that there is a beneficial relationship between football practice and bone health (Table ) in children, adolescents, adults, and older adults . Among children and adolescents, a 10‐month to 1‐year intervention significantly improves bone mineralization, bone mineral content, and bone stiffness .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results from the reviewed studies showed that there is a beneficial relationship between football practice and bone health (Table ) in children, adolescents, adults, and older adults . Among children and adolescents, a 10‐month to 1‐year intervention significantly improves bone mineralization, bone mineral content, and bone stiffness .…”
Section: Resultsmentioning
confidence: 99%
“…Osteoporosis is characterized by decreased bone mineral density and increased risk of fractures . The reviewed studies demonstrated a positive and significant association between bone health and RF among adolescents, adults, and older adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations